Discriminating between uncle-nephew and grandfather-grandson kinships by analyzing chromosomal sharing patterns. (December 2017) - Morimoto, Chie; Manabe, Sho; Fujimoto, Shuntaro; Hamano, Yuya; Tamaki, Keiji
Abstract: Relationships with the same degree of kinship (e.g., uncle-nephew and grandfather-grandson) are characterized by approximately the same amount of chromosomal sharing. Therefore, it is difficult to distinguish such relationships by commonly used short tandem repeat loci in forensic genetics. However, chromosomal sharing patterns are expected to differ between relationships, even when the same degree of kinship is present, by the frequency of recombination from common ancestors. In this study, we investigated the differences in chromosomal sharing patterns between uncle-nephew and grandfather-grandson pairs using high-density single nucleotide polymorphisms (SNPs). We computationally generated genotypes of 174, 254 autosomal SNPs in 249 uncle-nephew and grandfather-grandson pairs, while considering the effect of linkage disequilibrium between each SNP. We counted the number of shared chromosomal segments on the basis of identity by state regions. We then performed receiver operating characteristic curve analysis to evaluate the overlap between the number of shared segments in each relationship, and set a cut-off value. We also determined the relationship of actual related pairs genotyped by DNA microarray, based on the cut-off value. The number of shared segments in uncle-nephew pairs was larger than that in grandfather-grandson pairs. The area under the curve was 0.99954, indicating that the two relationships were clearly different. Relationships between almost all actual sample pairs were correctly determined by the cut-off value. Therefore, the number of shared chromosomal segments is a useful measure for discrimination between relationships with the same degree of kinship.